Development of Society as a Subject of Research - Meškauskas, Eugenijus (Problemos, 1978)
Methodological premises to study society development as a material process are considered. Among these are the Marxist specific feature of the dependence of material structure of society on the conditions of its existence in nature as well as the correlation between this structure and its institutional forms. In this connection a distinction between the general-sociological and historiographical problems of society history studies is pointed out.